2004
DOI: 10.1158/1078-0432.ccr-03-0666
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Oxaliplatin-Related Neurotoxicity by Calcium and Magnesium Infusions

Abstract: Purpose: Oxaliplatin is active in colorectal cancer. Sensory neurotoxicity is its dose-limiting toxicity. It may come from an effect on neuronal voltage-gated Na channels, via the liberation one its metabolite, oxalate. We decided to use Ca and Mg as oxalate chelators.Experimental Design: A retrospective cohort of 161 patients treated with oxaliplatin ؉ 5-fluorouracil and leucovorin for advanced colorectal cancer, with three regimens of oxaliplatin (85 mg/m 2 /2w, 100/2w, 130/3w) was identified. Ninety-six pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
178
0
10

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 311 publications
(198 citation statements)
references
References 16 publications
(19 reference statements)
8
178
0
10
Order By: Relevance
“…The bulk of evidence is negative for both scenarios [12], [14], [19], [20], with rare exceptions [17], [21]. Importantly, the large majority of studies have not used validated pain measurement tools [10], [11], [13], [14], [16], [19], [22], [23], while most have used the common terminology criteria (CTC) adverse events grading system as the primary outcome measurement. While this choice is sound and supported by robust evidence [24], it must be kept in mind that most patients with OXAIPN have small‐fiber‐predominant polyneuropathy [1], which has as its main symptom neuropathic pain.…”
mentioning
confidence: 99%
“…The bulk of evidence is negative for both scenarios [12], [14], [19], [20], with rare exceptions [17], [21]. Importantly, the large majority of studies have not used validated pain measurement tools [10], [11], [13], [14], [16], [19], [22], [23], while most have used the common terminology criteria (CTC) adverse events grading system as the primary outcome measurement. While this choice is sound and supported by robust evidence [24], it must be kept in mind that most patients with OXAIPN have small‐fiber‐predominant polyneuropathy [1], which has as its main symptom neuropathic pain.…”
mentioning
confidence: 99%
“…Retrospective study [250] Level III-2 161 3 cycles of FOLFOX every 2 weeks Grade 3 or 4 CIPN in Ca/Mg group recovered significantly quicker DBRCT [251] Level …”
Section: Magnesium / Calciummentioning
confidence: 99%
“…Magnesium and calcium infusions with oxaliplatin also showed initial positive results in a retrospective study [250]. Three clinical trials [251][252][253] reported that efficacy was not enhanced with one trial (n=174) being terminated due to the treatment group reporting a significant lower response rate compared to placebo [251].…”
Section: Magnesium and Calciummentioning
confidence: 99%
See 2 more Smart Citations